2′-Fluoro-modified phosphorothioate oligonucleotide can cause rapid degradation of P54nrb and PSF. Issue 9 (8th April 2015) - Shen, Wen; Liang, Xue-hai; Sun, Hong; Crooke, Stanley T.
Abstract: Synthetic oligonucleotides are used to regulate gene expression through different mechanisms. Chemical modifications of the backbone of the nucleic acid and/or of the 2′ moiety of the ribose can increase nuclease stability and/or binding affinity of oligonucleotides to target molecules. Here we report that transfection of 2′-F-modified phosphorothioate oligonucleotides into cells can reduce the levels of P54nrb and PSF proteins through proteasome-mediated degradation. Such deleterious effects of 2′-F-modified oligonucleotides were observed in different cell types from different species, and were independent of oligonucleotide sequence, positions of the 2′-F-modified nucleotides in the oligonucleotides, method of delivery or mechanism of action of the oligonucleotides. Four 2′-F-modified nucleotides were sufficient to cause the protein reduction. P54nrb and PSF belong to Drosophila behavior/human splicing (DBHS) family. The third member of the family, PSPC1, was also reduced by the 2′-F-modified oligonucleotides. Preferential association of 2′-F-modified oligonucleotides with P54nrb was observed, which is partially responsible for the protein reduction. Consistent with the role of DBHS proteins in double-strand DNA break (DSB) repair, elevated DSBs were observed in cells treated with 2′-F-modified oligonucleotides, which contributed to severe impairment in cell proliferation. These results suggest that oligonucleotides with 2′-F modifications can cause non-specific loss of cellular protein(s).